Avaliação dos efeitos ambientais da vegetação urbana sobre a qualidade de vida em Goiânia - Martins Júnior, Osmar Pires (2001)
This project is a study of the eco-system of the city of Goiânia (Goiás). Goiânia’s first Directive Plan was created according to the Garden City of Howard, one of the most important urban conceptions in the word. Using this plan and its urbanist evolution, one has tried to make a preliminary identification of the social agents, which produced the urban spaces of Goiânia. A classification and qualification of the open spaces and “green areas” of the city has been made. The quantity of vegetation (m².inhab.-1 ) and its quality (typing), when distributed adequately is important to the preservation of the urban eco-system, having important environmental effects on the quality of life of the population. The “green area” rate (Índice de Área Verde – IAV) is, therefore, one of the indicators of urban development. Changes in the open spaces, as indicators of IAV, in relation with changes in demographic density, indicative of human presence in the environment, have allowed the prevision of the amount of “green area” per urban inhabitant. The IAV calculated for Goiânia is 100,25 m². inhab.-1 , having suffered a per capita reduction of 17,68% in relation to the IAV established in the original city plan in 1938. In the next fifteen years it is possible forecast that the IAV will be 54,4% smaller than it is at the moment, decreasing to 45,71 m².inhab.-1 , if the privatization policy regarding publics spaces should persist. The “green areas” are unalienable and imprescriptible public property destined for common use. In spite of this, these areas have been decreasing over the years. The degree of deterioration of public assets has been calculated and constitutes a factor in the decay in urban life quality. The adoption of a programme to register and monitor the environmental assets of Goiânia is suggested, among other measures.